iCLEANED: Transforming livestock for a sustainable future. Process guide - Mwema, Emmanuel; Rein, Van Der Hoek; Notenbaert, An (2026)
The purpose of this process guide is to demonstrate how to navigate the iCLEANED tool environment to support effective modelling, interpretation and design of sustainable, profitable, and inclusive environmental assessments for livestock systems.